A tripartite approach to social inclusion in selected slums in Lagos State, Nigeria - Oluwaseyi Omowunmi Popogbe; Simeon Oludiran Akinleye; David Mautin Oke (Review of Economics and Political Science (REPS), 2023)
Purpose - This study aims to examine the social inclusiveness of slum dwellers by focusing on three key institutions which are social relations, government and the labour market. The literature emphasises the activities of these three institutions as indicators of social inclusion. Also, they accurately describe the social interactions of slum inhabitants at different levels. Design/methodology/approach - Three large slums (Makoko, Ilaje and Iwaya) in Lagos State were purposively selected for this study. Using a multi-stage sampling technique, there was the first level of cluster sampling across the communities and second-level random sampling of household heads in the clusters. In all, 400 respondents were sampled but 388 valid responses were used for the analysis. Findings - The study found minimal levels of inclusion in many of the indicators. However, Makoko had a higher degree of inclusion with respect to social relations and political participation compared to the other locations. Due to the poor level of governance, the resilience of slum dwellers has waned. Research limitations/implications - The study was limited to three of the largest slums in Lagos State. Moreover, due to threats of eviction in recent times, many respondents were reluctant to provide adequate answers to some of the questions asked. However, the responses gotten were adequate to provide appropriate awareness and relevant recommendations. Originality/value - The use of primary data made it possible for novel results to be generated on social inclusiveness in selected slums. The study extends the frontier of knowledge on social inclusion.
Keywords: I0; H7; I38; 330; Slums; Deprivations; Participation; Social inclusion